Cassava: improving sustainability of farming systems - Fermont, A. (2010)
This paper focuses on the cassava-maize cropping systems in East Africa, the benefits of cassava cultivation in improving soil fertility and different options in improving sustainability. The use of models to show the improvement of soil fertility when planting cassava and that cassava grows better in good soils are also highlighted.